Parameterization of heterogeneous reaction of SO2 to sulfate on dust with coexistence of NH3 and NO2 under different humidity conditions. (1st July 2019) - Zhang, Shuping; Xing, Jia; Sarwar, Golam; Ge, Yanli; He, Hong; Duan, Fengkui; Zhao, Yan; He, Kebin; Zhu, Lidan; Chu, Biwu
Abstract: Sulfate plays an important role in atmospheric haze in China, which has received considerable attention in recent years. Various types of parameterization methods and heterogeneous oxidation rates of SO2 have been used in previous studies. However, properly representing heterogeneous sulfate formation in air quality models remains a big challenge. In this study, we quantified the heterogeneous oxidation reaction using experimental results that approximate the haze conditions in China. Firstly, a series of experiments were conducted to investigate the heterogeneous uptake of SO2 with different relative humidity (RH) levels and the presence of NH3 and NO2 on natural dust surfaces. Then the uptake coefficients for heterogeneous oxidation of SO2 to sulfate at different RH under NH3 and NO2 coexistence were parameterized based on the experimental results and implemented in the Community Multiscale Air Quality modeling system (CMAQ). Simulation results suggested that this new parameterization improved model performance by 6.6% in the simulation of wintertime sulfate concentrations for Beijing. The simulated maximum growth rate of SO4 2− during a heavy pollution period increased from 0.97 μg m −3 h −1 to 10.11 μg m −3 h −1 . The heterogeneous oxidation of SO2 in the presence of NH3 contributed up to 23% of the sulfate concentration during heavy pollution periods. Graphical abstract: Image 1 Highlights: Uptake coefficients of SO2 on dust with coexistence of NH3 and NO2 were obtained. New parameterization was proposed based on experimental results under different RHs. The new parameterization can improve sulfate simulation in wintertime in CMAQ. Impact of NH3 on heterogeneous formation of sulfate in wintertime is non-negligible.